(v-8)(v-3)=0

Simple and best practice solution for (v-8)(v-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (v-8)(v-3)=0 equation:


Simplifying
(v + -8)(v + -3) = 0

Reorder the terms:
(-8 + v)(v + -3) = 0

Reorder the terms:
(-8 + v)(-3 + v) = 0

Multiply (-8 + v) * (-3 + v)
(-8(-3 + v) + v(-3 + v)) = 0
((-3 * -8 + v * -8) + v(-3 + v)) = 0
((24 + -8v) + v(-3 + v)) = 0
(24 + -8v + (-3 * v + v * v)) = 0
(24 + -8v + (-3v + v2)) = 0

Combine like terms: -8v + -3v = -11v
(24 + -11v + v2) = 0

Solving
24 + -11v + v2 = 0

Solving for variable 'v'.

Factor a trinomial.
(3 + -1v)(8 + -1v) = 0

Subproblem 1

Set the factor '(3 + -1v)' equal to zero and attempt to solve: Simplifying 3 + -1v = 0 Solving 3 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1v = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1v = 0 + -3 -1v = 0 + -3 Combine like terms: 0 + -3 = -3 -1v = -3 Divide each side by '-1'. v = 3 Simplifying v = 3

Subproblem 2

Set the factor '(8 + -1v)' equal to zero and attempt to solve: Simplifying 8 + -1v = 0 Solving 8 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1v = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1v = 0 + -8 -1v = 0 + -8 Combine like terms: 0 + -8 = -8 -1v = -8 Divide each side by '-1'. v = 8 Simplifying v = 8

Solution

v = {3, 8}

See similar equations:

| n+2.4=5.7 | | 2446566+929299856= | | 6s-10=2+3(-4)+(-4) | | x+3.2=6.8 | | r+15/8=57/8 | | (4x-9)(x-10)= | | 30+7x=4-x | | 10-5=8x+3 | | r+(1)5/8=(5)7/8 | | y+3/4=5/4 | | 3(-7)-9= | | 3x+4=3(x-2) | | z+17=35 | | 4x/2x+1-2x/2x+3=1 | | 6e^4x+3=12 | | 35-3c=19 | | 1+b=-11+7b | | -11-4x=5-8 | | .5(6+4)-.25(8x-12)=.5(2x-4) | | 8(-2x+8)+3x=155 | | (y+3)-(y-5)=7 | | 10-7x=6x+101 | | 5(y-3)+(2y-9)=8 | | y+2-2=15-2 | | f(-3)=-5 | | -6=n/2/10 | | 5-r/1.3=7.4 | | -120=-5(6-3v) | | 12q^2=4 | | 2(2x+9)-2=3(3x-8) | | t^2-70+8=0 | | 2(2x+9)-2=3(3x+8) |

Equations solver categories